2016
DOI: 10.1902/jop.2015.150455
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Disease in Individuals With a Genetic Risk of Developing Arthritis and Early Rheumatoid Arthritis: A Cross‐Sectional Study

Abstract: This study shows that individuals with pre-RA have significant inflammatory periodontal involvement. There was a significant association between IgG against P. gingivalis and ACPAs in pre-RA and markers of RA activity in individuals with eRA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
66
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(80 citation statements)
references
References 51 publications
9
66
0
5
Order By: Relevance
“…Although P gingivalis is not a marker of periodontitis, citrullination in the periodontium can be performed by the enzyme of this bacterium suggesting P gingivalis could be a possible link between periodontitis and RA as a mechanism of ending the patient's immunological tolerance . Increased concentrations of antibodies against P gingivalis before the onset of RA symptoms are associated with ACPAs and RA disease activity markers . Similarly, FDR has high periodontal involvement .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although P gingivalis is not a marker of periodontitis, citrullination in the periodontium can be performed by the enzyme of this bacterium suggesting P gingivalis could be a possible link between periodontitis and RA as a mechanism of ending the patient's immunological tolerance . Increased concentrations of antibodies against P gingivalis before the onset of RA symptoms are associated with ACPAs and RA disease activity markers . Similarly, FDR has high periodontal involvement .…”
Section: Discussionmentioning
confidence: 99%
“…Increased concentrations of antibodies against P gingivalis before the onset of RA symptoms are associated with ACPAs and RA disease activity markers . Similarly, FDR has high periodontal involvement . Obesity, ACPAs and periodontitis can be relevant conditions associated with the development of RA in FDR .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…P. gingivalis possesses a PAD enzyme that is capable of citrullinating fibrinogen and α-enolase, both of which are potential targets for ACPAs [69]. Indeed, in individuals with genetic risk factors for RA, antibodies to P. gingivalis have been associated with systemic RA-related autoantibodies [70, 71]. More recently, it has been shown that P. gingivalis PAD can undergo autocitrullination and that antibodies directed against this citrullinated form of PAD are more prevalent in RA patients compared to controls [72].…”
Section: Periodontal Tissue In Pre-symptomatic Rheumatoid Arthritismentioning
confidence: 99%
“…О связи между периодонтитом и разви-тием аутоиммунных нарушений, характерных для РА, сви-детельствует много фактов. У людей с генетическим рис-ком развития РА обнаружение антител к P. gingivalis в сы-воротке ассоциируется с гиперпродукцией АЦБ и РФ [147,148]. При РА обнаружен феномен аутоцитруллинирования ПАД P. gingivalis, ведущий к образованию антител к ПАД [149], который, однако, не характерен для «преклиниче-ской» фазы РА [150].…”
Section: фак торы внешней средыunclassified